SRI GREEN SUKUK AS A CONCEPTUAL FINANCING MODEL FOR ERADICATING ENERGY POVERTY IN INDONESIA: SRI GREEN SUKUK SEBAGAI MODEL PEMBIAYAAN KONSEPTUAL UNTUK MENGENTASKAN KEMISKINAN ENERGI DI INDONESIA - Ashhabul Manggala Sanggoleo Tosepu; Rifqi Aulia Pratama; Alya Rahma (Universitas Wahid Hasyim Semarang, 2026)
Energy poverty in Indonesia remains a multidimensional challenge, disproportionately affecting frontier, outermost, and underdeveloped (3T) regions despite a 99% national electrification ratio. The primary barrier has shifted from physical grid access to financial affordability, suppressing household productivity and straining the national budget through prolonged energy subsidies. This study aims to formulate a conceptual financing model utilizing Sustainable and Responsible Investment (SRI) Green Sukuk to address energy poverty efficiently and equitably. Adopting an exploratory qualitative design, this research combines a literature synthesis with conceptual modeling to propose a modified Wakalah-Ijarah Asset to be Leased contract, connecting government entities, a Special Purpose Vehicle (SPV), and investors to fund community-based renewable energy projects such as solar, micro-hydro, and biogas in 3T areas. To ensure holistic compliance with Islamic values, the model integrates a novel Composite Maqashid-SRI Impact (CMSI) mechanism, which operationalizes the five dimensions of Maqashid al-Shari'ah into measurable key performance indicators (KPIs) and requires projects to meet a minimum composite threshold for joint Green-SRI certification. The findings indicate that the integrated SRI Green Sukuk framework can bridge the fiscal gap in renewable energy infrastructure while mitigating transition risks, guaranteeing that the infrastructure delivers genuine social welfare, such as affordable communal tariffs (Rp1,500-2,000/kWh) and improved local productivity. By internalizing social impact into its core structure, this model provides a robust, Sharia-compliant pathway to eradicate energy poverty, foster sustainable regional development, and support Indonesia's equitable energy transition goals.